CONVERSION: A REASSESSMENT OF INSIGHT - Kadankavil, Thomas (Journal of Dharma, 2003)
The increasing fragmentation of world population under the banner of one or the other religion or ideology today goes side by side with the homogenization of cultural patterns and life style under the auspices of globalization. At the threshold of the dawn of new horizons of ideas it is not easy to determine the exact source of current ideologies. The indisputable worship of reason in modernity and the rejection of the overarching narratives in postmodernity have been somewhat challenged by the renewed assertion of the fundamentalist claims of Hindutva forces in India and the Christian and Islamic fundamentalist forces around the world. The question we examine in this article is how the polarization of people on mutually opposing intellectual positions on religious, moral, and philosophical truths is possible and how they could undergo change from one position to another after having subscribed to them for a long time intellectually and religiously. This process is not, of course, similar to the discarding of a scientific hypothesis in favour of another, which is established more firmly on the basis of clear evidence from the field of science, and so this issue does not come in the field of our reflection.